Legal implications of the use of Artificial Intelligence in personnel selection - Ramos Zaga , Fernando Antonio (2023)
The use of Artificial Intelligence has been revolutionizing several areas in society. In the business field, especially in personnel selection, it has been posing a series of legal challenges to companies despite its potential benefits. This article aims to identify the legal implications of the decisions made by Applicant Tracking Systems. To this end, the uses of AI and its application in personnel selection were analyzed, based on the legal analysis of the Personal Data Protection Law and the Guiding Principles established in said law. In sum, this article provides an overview of the legal implications regarding the use of AI in personnel selection and highlights the need for a rule regulating its use to ensure adequate legal protection measures.